INDIA DALAM DUNIA PENDIDIKAN - wanada rezeki (Jurnal Dinamika Pendidikan, 2020)
Education is a very important aspect for the country, because there will be quality human resources that will support the development and welfare of the country. India is the seventh largest country in the world with the largest population of around 600 million. With such a large amount, it is necessary to have a great effort in order to maximize the advantages of India. This was also done by India in the education sector where a 10-year free school policy and a ban on child labor were implemented.